The Role of Parents in Providing Sex Education to Children with Special Needs at SLB Putra Mandiri Kedungpring, Lamongan - Wida Sulistyowati; Muhammad Nurrohman Jauhari; Evi Aulia Nurahma (GRAB KIDS: Journal of Special Education Need, 2026)
This study aims to describe the role of parents in providing sex education to children with special needs (CSN) as an effort to prevent sexual violence. This research employed a qualitative approach with a phenomenological design. The research participants were parents of children with special needs at SLB Putra Mandiri Kedungpring, Lamongan. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using thematic analysis comprising data familiarization, reduction, categorization, theme identification, and conclusion drawing and verification. The results show that parents play an important role in introducing body parts and privacy, teaching gender differences, reinforcing toilet training and personal hygiene, and building open communication with their children as a form of sexual-violence prevention. However, several obstacles were found, such as limited parental understanding, feelings of embarrassment in discussing sexuality, and differences in children's abilities and communication modes. To overcome these constraints, parents applied personal, activity-based approaches, daily habituation, and informal cooperation with the school. This study concludes that parents play a crucial, though still developing, role in providing sex education for children with special needs, and that this role needs to be strengthened through structured guidance and closer collaboration with schools so that sexual-violence prevention can be implemented more effectively.